Evaluating the role of Ultraviolet Radiation and Ozone gas in reducing Aflatoxin in Rice (NTU Journal of Agriculture and Veterinary Science, 2024)
The use of chemicals to break down and reduce aflatoxin, including ozone gas, is the most efficient and effective in breaking down aflatoxin, followed by ultraviolet radiation, an effective physical method means of breaking down and reducing mycotoxins. Our study aims to find a way to reduce mycotoxins in some types of rice using ultraviolet radiation (U.V) and ozone gas ( O3) . The results showed that when all types of rice (white, kulbahar, amber) were exposed to ultraviolet radiation for 60 minutes, the reduction percentage of (25.00, 12.45, 11.76)%, respectively. When exposed to ozone gas for 10 minutes, the results showed the highest percentage of reduction in aflatoxin concentration (27.50, 26.01, 34.64)%, respectively.